La indexacion de las pensiones alimenticias en el Codigo de la niñez adolescencia - Hidalgo Torres, Sthefanie Andrea (2015)
The following research is focused on the issue of indexing stipulated in the Organic Code of Childhood and Adolescence, Title V, Chapter II; Art.43 (147.21) .- "Indexing Automatic Annual, since this law has generated a number of irregularities affecting the obligor and indirectly the fed. The annual maintenance without notice and without a claim automatic, has raised a number of drawbacks and does not consider the real economic status and income of the obligor as to afford the fees are updated automatically according to the National System of Census in Ecuador INEC, just this percentage adheres to the board of the defendant and often without a steady job or receive at least one with wage base salary, your rate rises canceled without chance to allege or disclose their real situation. Thus, many of the defendants when resorting to cancel their alimony are the big surprise of the new fee to cancel, thus generating dissatisfaction, apart from being totally unconstitutional because as we can see in our Constitution in the Articles 75 and 76 in terms of due process and helpless and totally contradicts this violates these rights in our Constitution. On the other hand we can argue that it is this law does not take into account many situations and realities in our country, as is unemployment not receive a satisfactory base salary or job security that ensures solvéntale economy simply this system is automatically generated without acquiring new information on the economic situation of the obligor. Therefore in this present work will try on the issue that has generated this product in: Art.43 (147.21) .- "IndexingAutomaticAnnualCode of Childhood and Adolescence.